Stereotactic Radiotherapy Followed by Surgical Stabilization Within 24 h for Unstable Spinal Metastases; A Stage I/IIa Study According to the IDEAL Framework - Versteeg, Anne L.; van der Velden, Joanne M.; Hes, Jochem; Eppinga, Wietse; Kasperts, Nicolien; Verkooijen, Helena M.; Oner, F. C.; Seravalli, Enrica; Verlaan, Jorrit-Jan (Frontiers in Oncology, 2018)
Background: Routine treatment for unstable spinal metastases consists of surgical stabilization followed by external beam radiotherapy (EBRT) or stereotactic body radiotherapy (SBRT) after a minimum of 1–2 weeks to allow for initial wound healing. Although routine treatment, there are several downsides. First, radiotherapy induced pain relief is delayed by the time interval required for wound healing. Second, EBRT often requires multiple hospital visits and only 60% of the patients experience pain relief. Third, spinal implants cause imaging artifacts hindering SBRT treatment planning and delivery. Reversing the order of surgery and radiotherapy, with dose sparing of the surgical area by SBRT, could overcome these disadvantages and by eliminating the interval between the two treatments, recovery, and palliation may occur earlier. Design: The safety of SBRT followed by surgical stabilization within 24 h for the treatment of unstable spinal metastases was investigated. Safety was evaluated using the Common-Toxicity-Criteria-Adverse-Events-4.0, with the occurrence of wound complications within 90-days being the primary concern. Results: Between June-2015 and January-2017, 13 patients underwent SBRT followed by surgical stabilization for unstable spinal metastases. The median time between SBRT and surgery was 17-h (IQR 5–19). None of the patients experienced wound complications. Improvements in pain and quality of life were observed over time for all patients. Conclusion: SBRT followed by surgical stabilization within 24 h for the treatment of unstable spinal metastases is safe. Palliation may be experienced earlier and with both treatments being performed in one hospital admission the treatment burden decreases.